The Digital Da’wah Movement: A Phenomenological Question of Urban Sufism Women - Jamalul Muttaqin (Tashwirul Afkar, 2021)
Today's socio-religious movement cannot be separated from the explosion of the era of modernism which demands a more dynamic, flexible and not rigid propaganda movement in dealing with the problems of people's lives. This phenomenon is marked by the rise of digital da'wah that comes into people's lives, particularly in Indonesia. The urban Sufism movement once emerged in response to this phenomenon, but what about women's urban Sufism? Where is their position today? This research uses a qualitative approach. Sources of data obtained from several books, journals, articles and other scientific works. More deeply, this paper will discuss the bibliography from time to time, from conventional forms of Sufism to urban Sufism. Either through religious tariqa, majlis dhikir, or certain religious institutions that today continue to flourish in Indonesia through digital media. Sufi groups are "spiritual" movements which have also contributed to the social and religious problems of society. Urban Sufism in urban areas especially in the movement of women Sufism is expected to be a spiritual mobility power that is presented as a new spectrum that is more ogled and heeded. Primarily there are two points that can be elaborated. First, try to elaborate on the emergence of the urban Sufism movement of women who throughout history have rarely been touched by the academic world even in the history of Sufism intellectual. Second, women's urban Sufism and the da'wah model and movement gave birth to the rise of power as a form of resistance to the perspective of the marginalization of Sufi women. This paper will further describe in detail from Sufism literature and some examples of urban women's Sufism movements in the era of modernism.